Inhibitors of the Fanconi anaemia pathway as potential antitumour agents for ovarian cancer - Sarah J Taylor; Mark J Arends; Simon P Langdon (Open Exploration Publishing Inc., 2020)
The Fanconi anaemia (FA) pathway is an important mechanism for cellular DNA damage repair, which functions to remove toxic DNA interstrand crosslinks. This is particularly relevant in the context of ovarian and other cancers which rely extensively on interstrand cross-link generating platinum chemotherapy as standard of care treatment. These cancers often respond well to initial treatment, but reoccur with resistant disease and upregulation of DNA damage repair pathways. The FA pathway is therefore of great interest as a target for therapies that aim to improve the efficacy of platinum chemotherapies, and reverse tumour resistance to these. In this review, we discuss recent advances in understanding the mechanism of interstrand cross-link repair by the FA pathway, and the potential of the component parts as targets for therapeutic agents. We then focus on the current state of play of inhibitor development, covering both the characterisation of broad spectrum inhibitors and high throughput screening approaches to identify novel small molecule inhibitors. We also consider synthetic lethality between the FA pathway and other DNA damage repair pathways as a therapeutic approach.